Spectrum policy and innovation: A Japanese perspective - Maria Bourna; Hitoshi Mitomo (International Telecommunications Society (ITS), 2014)
This paper investigates how spectrum policy affects the diffusion of innovation in the telecommunications sector, and is part of a general discussion on expanding spectrum policy aims to address sector innovativeness. We argue that innovation can be analytically depicted not only as the appearance of new technology, but also as physical network expansion of said technology, and adoption by end users. This definition is used in contrast with previous work on spectrum policy and innovation, which tends to use R&D or infrastructure investment as proxies for innovation, resulting in a more limited understanding of the innovation process. The study surveys the telecommunications industry in Japan over a period of 13 years (2001-2013), and discusses the effect of spectrum allocations and other regulatory acts on the expansion of the 3G mobile network. We found that spectrum policies excluding allocations had a negative effect on the expansion of the physical network, while the growth of said network correlated strongly with 3G penetration. This may suggest that the effect that spectrum policy has on innovation is most likely mediated by the role of competition in the infrastructure layer and is more pronounced in the contraction stage of the innovation life cycle. These results provide a preliminary basis for gaining a better understanding of the ways in which the policy environment relates to the evolutionary processes behind innovation.
Keywords: 330; Radio spectrum; Innovation; Japan; Telecommunications